COMPARATIVE ANALYSIS OF FOREIGN POLICY APPROACHES: CHINEESE PARTICIPATION IN THE UN PEACEKEEPING OPERAIONS (1981–2012) - I. A. Zarodov (Сравнительная политика)
Chinese approach towards peacekeeping evolved significantly through out the last few decades. Previous total denial in the 1980s transformed into acceptance of peacekeeping as valuable instrument of global governance. Since the beginning of 2000s peacekeeping emerge as integral component of Chinese global strategy, contributing to its national interests. As a result China significantly increased its participation in UN-led international operations.